Teachers’ Perception of Corrupt Practices at Teaching Service Commission in Nigeria - Shaibu, Leonard (Innovare Journal of Education, 2024)
Corruption is a global problem that has affected education in Africa and Nigeria, affecting the system’s efficiency. Two research questions guided this study. This study explored teachers’ perception of corrupt practices in the Teaching Service Commission (TSC) in Nigeria with particular reference to Ekiti state. A descriptive research design and a quantitative approach were adopted. Random sampling technique was used in this study and 180 participants were selected for this study. The study participants were given a questionnaire known as the Perceived Corrupt Practices Questionnaire (PCPQ) to obtain the views of the participants. The data collected was analyzed using descriptive statistics and percentages. The findings revealed many forms of corruption in the Ekiti State Teachers Service of Nigeria, including collecting official documents, bribery for admission to public schools and access preferences. Teachers also believe that corruption in the Board of Education is responsible for destroying social welfare and poor educational achievement in Nigeria. It was concluded that corruption reduces the resources available to schools, limits access to education, and reduces the quality of services in the state.